Interpreting the 20th century the struggle over democracy - Radcliff, Pamela Beth.; Teaching Company (Chantilly, Va. : Teaching Co., 2004)
Examines the struggle over democracy and the 20th century transformation of the political, social, and economic structures of the world.
lecture 1. Framing the 20th century -- lecture 2. The opening act: World War I -- lecture 3. Framing the peace: the Paris peace treaties -- lecture 4. Intellectual foundations: Nietzsche and Freud -- lecture 5. Art and the post-war crisis of meaning -- lecture 6. Gender crisis: the women question -- lecture 7. The origins of mass society -- lecture 8. Defining mass society and its consequences -- lecture 9. Crisis of capitalism: the Great Depression -- lecture 10. Communist ideology: from Marx to Lenin -- lecture 11. The rise of fascism -- lecture 12. Communist revolution in Russia. lecture 13. The totalitarian state? Nazi Germany -- lecture 14. The totalitarian state? The Soviet Union -- lecture 15. China: the legacy of imperialism -- lecture 16. The Chinese revolution -- lecture 17. India: the legacy of imperialism -- lecture 18. India: the road to independence -- lecture 19. Mexico: the roots of revolution -- lecture 20. The Mexican revolution and its consequences -- lecture 21. Japan: the path to modernization -- lecture 22. Japan: a new imperial power -- lecture 23. The Pacific war -- lecture 24. The European war. lecture 25. The Holocaust -- lecture 26. Existentialism in post-war Europe -- lecture 27. Origins of the Cold War -- lecture 28. The Cold War in American society -- lecture 29. Science and the state in Cold War America -- lecture 30. The welfare state -- lecture 31. The process of decolonization -- lecture 32. Challenges for post-colonial societies -- lecture 33. Competing nationalisms: The Middle East -- lecture 34. Development models: Communist China -- lecture 35. Development models: democratic India -- lecture 36. The authoritarian development state: Japan -- lecture 37. The Japanese model: available for export? -- lecture 38. Latin America: dictatorship and democracy -- lecture 39. Hard cases: Africa -- lecture 40. An African case study: NIgeria -- lecture 41. A generation of protests: civil rights -- lecture 42. A generation of protests: 1968 -- lecture 43. Global women's movements -- lecture 44. The rise of fundamentalist politics -- lecture 45. Communism: from reform to collapse, 1956-90 -- lecture 46. The end of history? -- lecture 47. Globalization and its challenges -- lecture 48. A new world order?
Lectures presented by Pamela Radcliff, University of California at San Diego.
DVD, region 1.
Keywords: Democracy -- History -- 20th century